Is Recent Exposure to Antibiotics a Risk Factor for Hospitalisation in Korean Children with Acute Non-Bacterial Gastroenteritis? A Nationwide Population-Based Study - Dongbum Suh; Hyuksool Kwon (MDPI AG, 2021)
The purpose of this study was to evaluate the effect of recent antibiotic therapy and probiotics on hospitalisation in children with acute gastroenteritis. Using a retrospective study design, data from the population aged up to 18 years were collected from the Korean National Health Insurance Service-National Sample Cohort. The duration of antibiotic therapy within 14 days of the index visit, prescription of probiotics at initial presentation, the effect size of antibiotic exposure on hospitalisation, and its modification by probiotics were assessed. Of 275,395 patients with acute gastroenteritis, 51,008 (18.5%) had prior exposure to antibiotics. Hospitalisation within 7 days of the index visit was positively associated with exposure to antibiotics (p-trend < 0.001). The prescription of probiotics (as a main effect; odds ratio, 0.80; 95% confidence interval 0.72-0.87) was associated with a decreased risk of hospitalisation. Prior exposure to antibiotics might be a significant risk factor for hospitalisation in children presenting with acute gastroenteritis. This may be favourably modified by administering probiotics at the initial presentation.